2020
DOI: 10.1021/acs.jchemed.9b00840
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Theory to Life: Learning Greener Electrochemistry by Taking Apart a Common Battery

Abstract: Electrochemistry is omnipresent in our lives, but students often do not recognize that the electrochemistry they learn in general chemistry happens in the batteries on which we depend. Students also may not recognize that they have the power to make greener choices about batteries using their knowledge of chemistry. This 4 h general chemistry laboratory activity challenges students to take apart a common battery, figure out how it works, map it to what they have learned about electrochemical cells in a general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…It’s incredible how it emits light in such a unique way!” Someone expressed, “I was thrilled to learn about the practical applications of semiconductors in our daily lives. It sparked my interest!” These observations align with prior research studies that highlight student preferences for courses incorporating practical, real-life contexts. , …”
Section: Course Evaluationssupporting
confidence: 87%
See 1 more Smart Citation
“…It’s incredible how it emits light in such a unique way!” Someone expressed, “I was thrilled to learn about the practical applications of semiconductors in our daily lives. It sparked my interest!” These observations align with prior research studies that highlight student preferences for courses incorporating practical, real-life contexts. , …”
Section: Course Evaluationssupporting
confidence: 87%
“…These observations align with prior research studies that highlight student preferences for courses incorporating practical, real-life contexts. 42,43 Societal Dimension Perceptions. The analysis revealed that up to 89.7% of students recognized the positive significance of their newly acquired semiconductor knowledge and skills, believing that it would enable them to act responsibly and confidently within society (4.44 ± 0.67).…”
Section: Assessment Of Chemistry Learning Relevancementioning
confidence: 99%
“…Electrochemistry is an important part of general and physical chemistry courses. Many electrochemistry laboratory experiments have been developed for laboratory instruction. Notable electrochemistry laboratory experiments are performed to explain galvanic cells because they are (i) low cost, , (ii) easy to assemble, and (iii) help build a standard reduction potential table. , A majority of these experiments involve the actual construction of electrochemical cells using metallic electrodes and their corresponding ionic solutions. In this demonstration, students can experience, visualize, and then understand rather than memorize basic concepts of electrochemistry such as electrons flowing from one metal electrode to another.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that in the context of an inquiry‐based lab, students improve their investigative skills (e.g. plan and describe procedure, making observations, collecting data, and analyzing results), and students propose ideas and engage in processes more reflective of authentic scientific processes (Domin, 1999; Keen et al, 2020; Walker et al, 2012). When comparing the attitudes between students in inquiry‐based labs and traditional labs, researchers found that students in inquiry‐based labs had a more positive attitude toward chemistry than students in traditional labs (Walker et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Gibson and Chase (2002) also found that inquiry‐based lab experiences can have positive long term effects on students’ interest in science. Other studies have shown that inquiry‐based labs can improve students’ self‐confidence in their lab skills and understanding of concepts (Gormally et al, 2009; Keen et al, 2020; Kloser et al, 2013). Walker et al (2012) found that students in both traditional and inquiry‐based laboratory sections significantly improved their performance on a chemical concept inventory, but there was no significant difference between the two groups on the inventory.…”
Section: Introductionmentioning
confidence: 99%